Beyond Numbers: Unveiling The Landscape of Taxpayer Motivation Through Meta-Analysis - Firmansyah, Amrie; Walzer, Michael (APSSAI ACCOUNTING REVIEW, 2025)
Research aims: This study aims to uncover the motivations behind taxpayer compliance through a meta-analytical approach and identify potential research gaps for future exploration. Design/Methodology/Approach: The research adopts a bibliometric analysis method to examine various global factors influencing tax compliance. Data were sourced from scientific journals published between 2019 and 2020, collected using the Publish or Perish 8 application, and further processed with Mendeley and VOSviewer. Research findings:  The findings indicate that tax compliance is shaped by economic, psychological, and social factors, each aligning with the Theory of Planned Behaviour framework Theoretical contribution/Originality: Provides a conceptual basis and data for the development of further academic research in the field of tax compliance. Practitioner/Policy implication: The insights generated from this study are expected to offer strategic value for the Indonesian government in formulating more effective fiscal policies, particularly to increase the tax ratio by deepening the understanding of compliance determinants